2019
DOI: 10.1038/s41598-019-42746-1
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of high glucose on mesangial cell-derived exosome composition, secretion and cell communication

Abstract: Mesangial cells stimulated with high glucose (HG) exhibit increased intracellular angiotensin II (AngII) synthesis that is correlated with the upregulation of AngII target genes, such as profibrotic cytokines. The intracrine effects of AngII can be mediated by several molecules transferred to other cells via exosomes (Exos), which play a key role in cellular communication under many physiological and pathological conditions. The aim of this study was to investigate the effects of exosomes derived from HG-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…In a similar way, hypoxia also increases the release of MPs from cancer 52 and non-cancer cultured cells such as endothelial cells 53 and human proximal tubular HK-2 cells (the current report). Regarding high-glucose, it has been found to increase the release of exosomes or MPs in several types of cultured renal glomerular cells 27,54,55 Given that hypoxia or high-glucose increase the release of extracellular vesicles in several types of cultured cell it is not surprising that in our experiments the incubation of PTC in HGHD conditions results in increased shedding of MPs. Unfortunately, the mechanisms involved in the increased release of MPs under hypoxia or high-glucose are still at an early stage of comprehension.…”
Section: Discussionmentioning
confidence: 56%
“…In a similar way, hypoxia also increases the release of MPs from cancer 52 and non-cancer cultured cells such as endothelial cells 53 and human proximal tubular HK-2 cells (the current report). Regarding high-glucose, it has been found to increase the release of exosomes or MPs in several types of cultured renal glomerular cells 27,54,55 Given that hypoxia or high-glucose increase the release of extracellular vesicles in several types of cultured cell it is not surprising that in our experiments the incubation of PTC in HGHD conditions results in increased shedding of MPs. Unfortunately, the mechanisms involved in the increased release of MPs under hypoxia or high-glucose are still at an early stage of comprehension.…”
Section: Discussionmentioning
confidence: 56%
“…Somatic gene transfer of the key detoxification enzyme glyoxalase 1 (Glo1) restored the proangiogenic capacity of diabetic EDCs suggesting a means of reversing diabetic cell dysfunction by interfering with the accumulation of reactive dicarbonyls. Interestingly, these changes occurred despite negligible effects on both the paracrine cytokine signature and survival of transplanted cells; suggesting that the fundamental changes wrought by chronic hyperglycemia must alter other cell secreted factors that promote endogenous cardiac repair (such as extracellular vesicles, EVs) 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…As such, those EVs generated in response to glomerular or tubular injury might be able to transfer survival and/or damage signals to neighboring or distant cells, promoting diverse biological effects. Several authors have studied the impact of metabolic stimuli, mainly high glucose (HG), in EVs release by glomerular [ 59 , 60 , 61 , 62 , 63 , 64 ] and tubular cells [ 65 ], and in their associated biological activities ( Table 1 ).…”
Section: Biological Effects Of Evs On Renal Cellsmentioning
confidence: 99%
“…Indeed, GMC-derived EVs were similar in size, but not in number, in HG-stimulated cultures compared to controls, exerting different biological effects. As such, the co-incubation of GMCs with mesangial HG-EVs resulted in the production of higher levels of fibronectin, angiotensinogen, renin, Angiotensin II type (AT)1 and AT2 receptors in GMCs, indicating their possible role in kidney cell dysfunction [ 64 ]. In contrast, Barutta et al reported a reduction in the number of GMC-EVs by HG compared to control cultures, which were enriched in miR-145 [ 63 ], while others found no differences in miR-192, -194 or -215 despite HG treatment [ 70 ].…”
Section: Biological Effects Of Evs On Renal Cellsmentioning
confidence: 99%